An Application Deployment to Openshift Cloud Using Existing Git Repository From Local Client (International Journal of Engineering and Computer Science, 2015)
Cloud is capable of running many kinds of applications. Putting application to some clouds are free and had their ownprocedure. Few clouds are famous for their services and OPENSHIFT, a Red Hat Cloud, is one of that cloud service provider which isconstantly providing good services thus famous one for individual application deployment. Keeping personal development in mind here weare describing complete procedure to deploy application to OPENSHIFT cloud. For deployment first create a small application in HTML orPHP then application is connected to the newly created GIT repository. GIT repository is then connected to the OPENSHIFT account.Cloud deployment will provide a link which can be used to access your application. Application is successfully running over cloud thusavailability to your project anywhere. Deploying application to cloud will provide the access anywhere ease. This deployment will teach theprocedure to manage big applications and also this procedure will reflect immediate change in cloud when applications edited at localmachine. This will help developers, researcher, and student to start with the very popular concept of cloud.